Primary health and emergency care network: interfaces in health regions in Brazil and Canada - Uchimura, Liza Yurie Teruya (2019)
Introduction: There are many factors to be identified and flows to be established in the interface between primary care and the emergency care network. Comparing different health systems with processes of health policies based on regionalization can result in new health planning instruments. In this sense, understanding the regional arrangements and dynamics of the Canadian health system in a comparative study with the Brazilian reality enabled the implementation of strategies for the development of innovations and health management planning in Brazil. Objective: To identify the factors that interfere in the establishment of primary care and emergency care network interfaces in different socio-spatial realities (regions) and in different health systems. Methods: Two case studies: in Brazil, using mixed methods and in Canada, qualitative methods. The study in the North-Barretos and South-Barretos regions (São Paulo, Brazil) consists of interviews with key informants and analysis of secondary data. In the Mississauga Halton Local Health Integration Network and Toronto Central Local Health Integration Network (LHIN) (Ontario, Canada) interviews were conducted with key informants. The data from the structured questionnaires were tabulated using the PHP Line Survey - Open Source software. Statistical calculations were performed using SPSS Statistics for Windows, Version 22.0. Thematic analysis of the qualitative data (interviews with open-ended questions, meeting minutes and documents) was carried out in Atlas-ti software. The results of the case studies were analyzed independently and, finally, compared to identify their differences and similarities. The study was approved by the Ethics Committee of the University of São Paulo Faculty of Medicine, under process number 045/16. Results: Aspects of policy, structure and organization interfere at different levels between primary care and the emergency care network in the regions selected for this study. Regionalization as a dimension of health policy has presented satisfactory results for planning, decision making, and resource management focused on health needs, but has been insufficient for the integration of primary care and the emergency care network. Barriers and facilitators, at policy, structural and organizational levels, were identified for the integration of primary care and the emergency services in the studied regions. Conclusion: Health managers should recognize the interfaces and integrate the different health services and share knowledge and population health diagnoses. Fragmented health management is reflected in fragmented health care. To achieve effective integration among health services, stakeholders and policy makers should prioritize better management performance, effective teamwork forums, leadership training, and monitoring programs for each dimension of integrated care